STUDY OF THE INFLUENCE OF DOOR INTRUSION VELOCITY IN LATERAL COLLISIONS: BIOMECHANICAL RESULTS - Rodrigues, Rafael Costa; Amaral, Henrique da Cruz; Melo, Jordana Lais Vimieiro; Rezende, Fabrício Cardinali; Campos, Frederico Rodrigues; Magalhães, Pedro Américo Almeida (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The influence of door intrusion velocity in occupant injury according to Latin NCAP side impact 2016 protocol were studied isolating door panel design or clearance between occupant versus door panel with the main objective of understand purely structural features in a mobile deformable barrier side impact. A sled impact model was created with the validated MADYMO fiftieth percentile occupant model (EuroSid 2) and a finite element flat panel. Impact velocity was incremented from 3.5 to 9.5m/s in intervals of 1m/s. Occupant injury was measured for each case analyzing ribs, abdomen and pelvis behavior to identify a critical intrusion velocity according to project characteristic and its objectives.